2010
DOI: 10.1029/2010sw000581
|View full text |Cite
|
Sign up to set email alerts
|

Comparing geosynchronous relativistic electron prediction models

Abstract: 1] Extended periods of relativistic electron intensity at geosynchronous orbit can create severe deepcharging hazards for satellites. Over the last 20 years a number of models have been developed to predict electron flux levels using solar wind and geomagnetic indices as inputs. We analyze the results of several of these including the Relativistic Electron Forecast Model based on the linear prediction filter technique, a neural network algorithm, and the physics-based diffusion method. Analyses using the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…This model assumes no particular acceleration method but only recognizes that the solar wind is the ultimate driver of relativistic electron flux variations. Finally, Perry et al [2010] conducted a comparative study of three different outer belt forecasts: NOAA's REFM, Li [2004], and the Air Force's FluxPred model [ Ling et al , 2010]. FluxPred is a neural network model using 17 inputs consisting of the past 10 days of GEO flux data and 7 days of Kp.…”
Section: Introductionmentioning
confidence: 99%
“…This model assumes no particular acceleration method but only recognizes that the solar wind is the ultimate driver of relativistic electron flux variations. Finally, Perry et al [2010] conducted a comparative study of three different outer belt forecasts: NOAA's REFM, Li [2004], and the Air Force's FluxPred model [ Ling et al , 2010]. FluxPred is a neural network model using 17 inputs consisting of the past 10 days of GEO flux data and 7 days of Kp.…”
Section: Introductionmentioning
confidence: 99%
“…By fitting Model separately for each year, we are able to detect that parameter estimates change over time. The time‐varying functional relationship between log electron flux and solar wind speed has been noted in the literature [e.g., Reeves et al , ; Perry et al , ; Turner et al , ; Kellerman et al , ]. Reeves et al [] graphically examined the long‐term variations between solar wind speed and log electron flux and concluded that the functional relationship between these two variables is not constant in time.…”
Section: Parameter Estimate Sensitivity To Training Datamentioning
confidence: 99%
“…Reeves et al [] graphically examined the long‐term variations between solar wind speed and log electron flux and concluded that the functional relationship between these two variables is not constant in time. Perry et al [] compared the accuracy of models forecasting log electron flux between 1996 and 2008. They note that the worst forecasts occurred during solar maximum (second half of 1999 through first half of 2002), better forecasts during the declining years of solar minimum (second half of 2002 through 2008), and their best forecasts during the inclining years of solar minimum (1996 through first half of 1999).…”
Section: Parameter Estimate Sensitivity To Training Datamentioning
confidence: 99%
“…As a check of how well the model performs in relation to other models, the performance of the FLUXPRED model is compared with that of the REFM model, a fluence forecasting model which is based on a linear prediction filter algorithm developed by Baker et al [1990] and refined by the Space Weather Prediction Center of the National Oceanic and Atmospheric Administration (NOAA/SWPC) (http://www.swpc.noaa.gov/refm/REFMDoc.html). A more comprehensive comparison with the REFM model and other models will be discussed in a companion paper [ Perry et al , 2010]. The REFM model was run with input consisting of 30 days of 5 minute > 2 MeV electron flux data and 30 days of 1 h solar wind data.…”
Section: Model Performancementioning
confidence: 99%